EL LIDERAZGO DOCENTE Y DIRECTIVO EN LOS PROGRAMAS TÉCNICOS-TECNOLÓGICOS DE LA UNIVERSIDAD COOPERATIVA DE BUCARAMANGA (COLOMBIA) - Cuadros, Mª del Pilar Jaime; Reche, Mª del Pilar Cáceres; García, Santiago Alonso (European Scientific Journal, ESJ, 2015)
The University of Granada developed research efforts in the field of leadership and organizational development, allowing this research in the Cooperative University of Colombia. The present study aims to recognize types of Leadership in teachers and principals, in order to identify achievement strategies that can improve the educative center and organization. To this aim we conducted a descriptive research qualitative techniques, as interview developed to students and focus group to professors. Results show the coexistence of transformational, transactional and corrective leaderships, as well as, students highlight the presence of charisma, motivation, vision, clear objectives, error monitoring and reward for achievement. So, it is observed the importance of knowing the context, in this case, university context to let an appropriate leadership and successful for institution, according to different situations, aims or groups.